2021
DOI: 10.1371/journal.pone.0254654
|View full text |Cite
|
Sign up to set email alerts
|

Availability of preoperative neutrophil-lymphocyte ratio to predict postoperative delirium after head and neck free-flap reconstruction: A retrospective study

Abstract: Postoperative delirium (POD) is a well-recognized postoperative complication and is associated with increased morbidity and mortality. We investigated whether the preoperative neutrophil-lymphocyte ratio (NLR) could be an effective predictor of POD after head and neck free-flap reconstruction. This was a single-center, retrospective, observational study. We analyzed the perioperative data of patients who had undergone elective head and neck free-flap reconstruction surgery. POD was assessed with the Intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…This can be interpreted as the NLR may be the more effective inflammatory marker in early detection of delirium occurrence, compared to CRP (Figure 5). This result is in line with recent studies using NLR for prediction of delirium (31,32).…”
Section: Discussionsupporting
confidence: 93%
“…This can be interpreted as the NLR may be the more effective inflammatory marker in early detection of delirium occurrence, compared to CRP (Figure 5). This result is in line with recent studies using NLR for prediction of delirium (31,32).…”
Section: Discussionsupporting
confidence: 93%
“… 22–24 Recent studies found that preoperative NLR can be a predictive factor for POD after head and neck free-flap reconstruction, total hip arthroplasty, esophagectomy, and carotid endarterectomy. 4 , 5 , 7 , 9 In this study, both preoperative NLR and postoperative NLR were higher in patients with POD after lower limb fracture than those in patients without POD. Multivariate analyses revealed that among the hematological biomarkers examined, postoperative NLR was still associated with the development of POD.…”
Section: Discussionmentioning
confidence: 46%
“…Some of this can be attributed to the exclusion of patients with preoperative delirium, as some relative studies did not include this exclusion criteria. 4 , 7 , 9 In addition, change of NLR (postoperative value− preoperative value) in the POD group was significantly higher than that in the non-POD group and was positive value, which meant that NLR in patients with POD increased significantly after surgery. This result may indicate more severe systemic inflammation and neuroinflammation caused by surgery and anaesthesia in patients with POD.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We reported that higher preoperative NLR was associated with the development of postoperative delirium that is also caused by neuroinflammation 6 , 7 . In addition, several studies reported that the NLR and the PLR were associated with generated psychiatric diseases, schizophrenia, attention-deficit/hyperactivity disorder (ADHD), and epileptic seizure 8 10 .…”
Section: Introductionmentioning
confidence: 92%